2018
DOI: 10.1016/j.celrep.2018.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Transcription Factor Induction Mediates Hemogenic Reprogramming

Abstract: SUMMARY During development, hematopoietic stem and progenitor cells (HSPCs) arise from specialized endothelial cells by a process termed endothelial-to-hematopoietic transition (EHT). The genetic program driving human HSPC emergence remains largely unknown. We previously reported that the generation of hemogenic precursor cells from mouse fibroblasts recapitulates developmental hematopoiesis. Here, we demonstrate that human fibroblasts can be reprogrammed into hemogenic cells by the same transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 62 publications
(91 reference statements)
5
46
0
Order By: Relevance
“…Enrichment tests were performed for custom gene sets extracted from prior literature and for gene sets associated with specific gene ontology (GO) terms [44,45]. RNAseq data from Gomes et al [30] was used for comparative purposes. Normalized read counts for all relevant samples were plotted using GRAPH-PAD PRISM 7 software.…”
Section: Rnaseq Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Enrichment tests were performed for custom gene sets extracted from prior literature and for gene sets associated with specific gene ontology (GO) terms [44,45]. RNAseq data from Gomes et al [30] was used for comparative purposes. Normalized read counts for all relevant samples were plotted using GRAPH-PAD PRISM 7 software.…”
Section: Rnaseq Analysismentioning
confidence: 99%
“…We recently demonstrated that three TFs, GATA2, GFI1B, and FOS, were sufficient to induce a hemogenic program in human fibroblasts [30]. Transplantation of CD49f + cells sorted at Day 25 of reprogramming in immunocompromised mice resulted in short-term multilineage engraftment.…”
Section: Gfi1 Added To the Ggf Cocktail Expands The Derived Hspc Poolmentioning
confidence: 99%
See 3 more Smart Citations